Evapotranspiração, crescimento e produção do sorgo em cultivo irrigado na região do baixo açu-RN - Fonsêca Neto, Joacy (Universidade Federal Rural do Semi-Árido, 2013)
The sorghum crop (Sorghum bicolor L. Moench) in the context of agriculture in semiarid northeast has been outstanding every day, due to the higher very possibilities to solve the problem of shortage of energy source in this region, because of high productivity, good suitability for mechanization, resistance to drought, reduced requirement of soil and therefore fewer risks and higher net revenue, as an alternative to the corn crop which has more demanding compared to sorghum. The Brazilian semiarid region characterized by water scarcity, become indispensable use of irrigation for most crops can produce satisfactorily. Given the above, this study aimed to determine the crop evapotranspiration (ETc ) and crop coefficient (Kc) for different growth stages of sorghum dual purpose (forage and grain) called BRS - Ponta Negra, as well as evaluating the growth, development and production in irrigated under the climatic conditions of the city of Ipanguaçu/RN. The work was conducted in the experimental area of EMPARN irrigation sprinkler was used and grown in single rows spaced 0.75 m between rows and 0.10 m between plants. The measurement of ETc was performed using two weighing lysimeters identical, with an area of 2.7 m² (dimensions of 1.5 x 1.8 m in area and 0.9 m deep). The reference evapotranspiration (ETo) was estimated by the FAO Penman-Monteith method and necessary to estimate climate data were collected by an automatic meteorological station installed in the area between the two lysimeter. The total crop cycle Sorghum Ponta Negra was 96 days, with an evapotranspiration of 499.89 mm. The crop coefficients (Kc) were found (Phase I - 0.49; Phase II - 0.82, phase III - 1.13; Phase IV - 0.98) with length of time of 21, 36, 27 and 12 days, respectively. The fresh weight was 84.42 ton was ha-1, while the productivity of grains found was 8,72 ton was ha-1 and the dry matter of 35,9 ton was ha-1
Evapotranspiration, growth and yield of sorghum under irrigated cultivation in the Açu-RN valley region
Keywords: irrigation; Weighing lysimeter; productivity; Sorghum bicolor Moench; Irrigação; Lisímetro de pesagem; Produtividade; Sorghum bicolor Moench; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM